Vacuum brazing of dissimilar Al 7075 and Al–25 Si alloy - Liu, Dashuang (2023)
The vacuum brazing of dissimilar Al 7075 and Al–25 Si alloy was investigated. The brazing filler was copper foil with a thickness of 20 µm, and the brazing temperature was 560◦ C held for 10 min. The average shear strength of the brazed joint of dissimilar Al 7075 and Al–25 Si alloy was 26.4 MPa. The copper layer was found to be dissolved completely, and the interface of the joint had an irregular shape with a serrated border, indicating a good metallurgical bonding between the two dissimilar alloys. However, factors which might cause deterioration of the shear strength were also observed, including the formation of the intermetallic compounds such as MgZn2, Cu2 Al and Mg2 Si, the existence of voids and microcracks, the coarsening of grains in Al 7075, and the coarsening of primary Si in Al–25 Si alloy.